Mapping mechanisms and growth regimes of magnesium electrodeposition at high current densities. Issue 3 (3rd December 2019) - Davidson, Rachel; Verma, Ankit; Santos, David; Hao, Feng; Fincher, Cole D.; Zhao, Dexin; Attari, Vahid; Schofield, Parker; Van Buskirk, Jonathan; Fraticelli-Cartagena, Antonio; Alivio, Theodore E. G.; Arroyave, Raymundo; et al.
Abstract : Galvanostatic electrodeposition from Grignard reagents in symmetric Mg–Mg cells is used to map Mg morphologies from fractal aggregates of 2D nanoplatelets to highly anisotropic dendrites with singular growth fronts and entangled nanowire mats. Abstract : The utilization of metallic anodes holds promise for unlocking high gravimetric and volumetric energy densities and is pivotal to the adoption of 'beyond Li' battery chemistries. Much of the promise of magnesium batteries stems from claims regarding their lower predilection for dendrite growth. Whilst considerable effort has been invested in the design of novel electrolytes and cathodes, detailed studies of Mg plating are scarce. Using galvanostatic electrodeposition of metallic Mg from Grignard reagents in symmetric Mg–Mg cells, we establish a phase map characterized by disparate morphologies spanning the range from fractal aggregates of 2D nanoplatelets to highly anisotropic dendrites with singular growth fronts and nanowires entangled in the form of mats. The effects of electrolyte concentration, applied current density, and coordinating ligands have been explored. The study demonstrates a complex range of electrodeposited morphologies including canonical dendrites with shear moduli conducive to penetration through typical polymeric separators. We further demonstrate a strategy for mitigating Mg dendrite formation based on the addition of molecular Lewis bases that promote nanowire growth through selective surface coordination.